The photography-immersion-value nexus: A quantitative model for enhancing tourist experiences - Khondabi, H.; Dias, A.; Pereira, L. (Cases on innovation and sustainability in tourism, 2024)
Tourist photography is common, yet its impact on experience remains unclear. This research explores how photography fosters immersion, enhancing enjoyment, memory, and perceived authenticity. A quantitative model tested via online survey reveals photography’s positive influence on tourist value (functional, emotional, memorial, social). It recommends destination managers leverage photography while preserving attractions’ natural essence and authenticity. The majority of the hypotheses grounded on the literature review were supported, and the achieved results showed that tourism photography contributes to tourists’ immersion and such occurrence impacts their involvement, memorability, and authenticity of their visiting experience. Moreover, each of the experience components enhance the value perception dimensions, which are functional, emotional, memorial, and social values.